CRAC channels drive digital activation and provide analog control and synergy to Ca 2+-dependent gene regulation - Kar, P; Nelson, C; Parekh, AB (2012)
Ca 2+-dependent gene expression is critical for cell growth, proliferation, plasticity, and adaptation [1-3]. Because a common mechanism in vertebrates linking cytoplasmic Ca 2+ signals with activation of protein synthesis involves the nuclear factor of activated T cells (NFAT) family of transcription factors [4, 5], we have quantified protein expression in single cells following physiological Ca 2+ signals by using NFAT-driven expression of a genetically encoded fluorescent protein. We find that gene expression following CRAC channel activation is an all-or-nothing event over a range of stimulus intensities. Increasing agonist concentration recruits more cells but each responding cell does so in an essentially digital manner. Furthermore, Ca 2+-dependent gene expression shows both short-term memory and strong synergy, where two pulses of agonist, which are ineffectual individually, robustly activate gene expression provided that the time interval between them is short. Such temporal filtering imparts coincidence detection to Ca 2+-dependent gene activation. The underlying molecular basis mapped to time-dependent, nonlinear accumulation of nuclear NFAT. Local Ca 2+ near CRAC channels has to rise above a threshold level to drive gene expression, providing analog control to the digital activation process and a means to filter out fluctuations in background noise from activating transcription while ensuring robustness and high fidelity in the excitation-transcription coupling mechanism. © 2012 Elsevier Ltd All rights reserved.